The Campaigns of the First Three Years of Tukultī-Ninurta’s I (1242-1206 BC) - Ruslan Tsakanyan (Banber Arevelagitut'yan Instituti, 2025)
The chronology of events during the reign of Tukultī-Ninurta I does not stand out with particular accuracy, which often sparked controversy. In particular, it refers to the irregular sequence of events in the king's records. In this article, examining the records of the Assyrian king, we have singled out the raids of his first three years, 1242-1239 BC․